Taxonomy and phylogeography of the Freshwater Halfbeak, Genus Hemirhamphodon in Sundaland River Basin by Combined Molecular and morphological approaches. - Mohd Nor, Siti Azizah (Universiti Sains Malaysia, 2014)
A detailed systematics, taxonomy and phylogeography study of the halfbeak fishes, genus Hemirhamphodon and population genetics of H. pogonognathus in the Sundaland paleo-drainages of Siam, Malacca Strait, North Sunda and East Sunda was conducted. Based on a 678 bp partial mitochondrial DNA cytochrome b (cyt b) and 219 bp of tRNA-Glu gene and two nuclear DNA loci (SCNP: Hp5 and Hp54), 15 and 10 individuals per site were amplified in 18 populations from Peninsular Malaysia, Borneo (Sarawak) and Sumatra within the paleo- drainage region